Determinants of Willingness to Pay for Improved Solid Waste Management System in Lekhnath, Kaski, Nepal - Dhungana, Ananta Raj (Janapriya Journal of Interdisciplinary Studies, 2018)
Solid waste management is one of the developmental challenges facing city authorities worldwide, especially in most developing countries. Rapid urbanization has made solid waste management a serious problem in poor and developing countries. This study aims to analyze the determinants of willingness to pay for improved solid waste management system. For this purpose, two hundred and seventeen Households were selected in Lekhnath, Kaski, Nepal. Pre-structured questionnaire was used to collect the data. Data was collected by using systematic random sampling techniques. Multiple Linear Regression analysis was used to find the determinants of willingness to pay for improved solid waste management system. The tentative average wastes produced per day from their house is one kilogram with minimum one hundred gram and maximum ten kilogram per day. Main disposal method/site for solid waste management of majority of the respondents is Burn followed by cannal, near open places, send in waste management vehicle, road side and rivulets. Almost all of the respondents are not satisfied with the community responsible for solid waste management in the study area. The average amount that the respondents have willingness to pay for solid waste management system is Rs 56.84 per month. Further, it is found that Having any member abroad, Remittance received in last one year and House ownership are the major determining factors for willingness to pay for improved solid waste management system in the study area. However, other factors like Sex of the respondents, age of the respondents, family size, Family type, Caste/ethnicity, education of the respondents, Total number of employed person at home, Total number of literate person at home, Major occupation of the respondents, tentative weight of accumulated solid waste per day, Monthly Income of household, Visit at any hotel/restaurant during last 12 months, and Having any livestock at household do not have any significant impact on willingness to pay for improved solid waste management system. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017)